Impacts of climate, land use, and land cover change on the distribution of squirrels in Nepal - Dahal, Dibya Raj; Thapa, Sanjan; Koprowski, John L. (Nepalese Journal of Zoology, 2025)
Squirrels are one of the least studied mammalian faunas in south Asia. Squirrels are habitat-specialists and therefore are sensitive to changes in climate and land cover. Therefore, it is necessary to understand the impact and conservation implications of climate and land cover change. We used species distribution modelling to predict the distribution of species in suitable habitats and the impacts of future climate change. Three species of squirrels that prefer heterogeneous arboreal habitat and have high occurrence records were assessed through maximum entropy modelling. Eight uncorrelated bioclimatic variables and six Euclidean distances of land used and land cover change were used for MaxEnt modelling under current and four different scenarios of climate change. For two species (Callosciurus pygerythrus and Petaurista magnificus) the maximum and minimum possible areas of habitat suitability under the current climatic scenario were predicted in Nepal. The distribution of suitable habitats for all representative species of squirrels was predicted from eastern to central Nepal, due to no record of baseline data. Habitat suitability of three species of squirrels is projected to change by 2050 and 2070 under SSP4.5 and SSP8.5 scenarios, contingent on climate and land used and land cover change. In the future, suitable distribution range of the habitat of C. pygerythrus is predicted to shrink, whereas the distribution ranges of suitable habitat of Dremomys lokriah and P. magnificus predicted to expand. This is the first study targeted the distribution modeling of squirrels in Nepal. The results from this study inform future surveys and highlight the importance of monitoring needs for the conservation of squirrels throughout Nepal.